Men and Those With a History of Smoking Are Associated With the Development of Postoperative Ileus Following Elective Colorectal Cancer Resection at a Private Academic Hospital in Johannesburg, South Africa: A Retrospective Cohort Study - Watkins, Estella L.; Schellack, Natalie; Abraham, Veena; Bebington, Brendan (Frontiers in Surgery, 2021)
Introduction: A scarcity of local published data on colorectal cancer (CRC) postoperative complications including postoperative ileus (POI) exist. POI is a temporary gastrointestinal (GI) state of absent or reduced gastric motility shown to increase patient morbidity, prolong length-of-stay (LOS) and intensify the healthcare resource burden. The pathogenesis of POI involves a neurogenic- and inflammatory phase plus a pharmacological component. Aim and objectives: This study aimed to determine centre-specific preoperative risk factors associated with the development of ileus post elective therapeutic CRC resection. The objectives were to determine whether patient demographics; functional status; comorbidities; GI history; pharmacotherapy including neoadjuvant chemotherapy and lastly neoadjuvant radiation and chemoradiation were associated with the development of POI. Method: Patients who underwent CRC resection between January 2016 and May 2019 were retrospectively identified from an existing database. Urgent—or non-therapeutic surgeries; surgeries with the complication anastomotic leak or GI obstruction; patients under 18 at the time of surgery or surgeries preceded by preoperative parenteral nutrition were excluded. A comparison was done of the incidence of exposure in the study cohort to investigated variables as potential risk factors for the complication POI. Results: A total of 155 patient cases were included, and 56 (36%) of them developed POI. Univariate comparison of patients who developed POI with demographic characteristics of patients who didn’t, suggested that females were at lower risk to develop POI compared to males (p=0,013; RR 0,56; 95% CI 0,36-0,89). Functional status suggested that all previous smokers were at a higher risk to develop POI compared to lifetime non-smokers (p=0,0069; RR 1,78; 95% CI 1,17-2,70). Multivariable comparison of ≤ 5 qualifying parameters showed no significance. Conclusion: The high local incidence of POI in this patient population shows that intervention is required to reduce the POI rate and improve postoperative outcomes. This study suggests that for male patients and all patients with a history of smoking, CRC resection preoperative recommendations with the intention to prevent POI should include instructions initiating the activation of preventive strategies like the Enhanced Recovery After Surgery (ERAS) programme. More studies are needed to adequately determine local perioperative risk factors for POI.